Am I still not a man and a brother?: protest memory in contemporary antislavery visual culture - Trodd, Zoe (Taylor & Francis, 2013)
This article examines the visual culture of the twenty-first century antislavery movement, arguing that it adapts four main icons of eighteenth- and nineteenth-century abolitionism for its contemporary campaigns against global slavery and human trafficking: the ‘Am I Not a Man and a Brother’ icon, the diagram of the ‘Brookes’ slave ship, the ‘Scourged Back’ photograph and the auction-block detail from the Liberator masthead. Finding some of the same limitations of paternalism, dehumanisation and sensationalism as dominated much of the first antislavery movement’s visual culture, the article nonetheless identifies a liberatory aesthetic and a protest memory in the antislavery imagery of several contemporary artists, including Charles Campbell and Romuald Hazoume`.